2017
DOI: 10.9741/23736658.1055
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs in advance care planning among Chinese Americans: Similarities and differences between the younger and older generations

Abstract: The purpose of this research is to explore behavioral, normative, and control beliefs in the discussion of advance care planning (ACP) among older and younger Chinese Americans. Ethnic minority groups have been identified as less engaged in ACP and this represents an ethnic and cultural gap. Older Chinese American adults often have different beliefs and values compared to the younger generation who are more acculturated to American mainstream culture. These differences may hinder the discussion of ACP with Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…This may be because the foreign-born Chinese Americans have lower socioeconomic status, less English proficiency, lower levels of acculturation, and less knowledge about ACP and the US healthcare system than their US-born counterparts. 11 , 12 , 22 In addition, these individual-level differences may be mixed with other system-level barriers within the US healthcare system to worsen the disparities in ACP engagement. 23 For example, Chinese American immigrants may have a stronger belief that family and society are held in higher regard than individuals, and attribute a higher value to collectivism of family and society rather than patient autonomy in EOL decision making.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be because the foreign-born Chinese Americans have lower socioeconomic status, less English proficiency, lower levels of acculturation, and less knowledge about ACP and the US healthcare system than their US-born counterparts. 11 , 12 , 22 In addition, these individual-level differences may be mixed with other system-level barriers within the US healthcare system to worsen the disparities in ACP engagement. 23 For example, Chinese American immigrants may have a stronger belief that family and society are held in higher regard than individuals, and attribute a higher value to collectivism of family and society rather than patient autonomy in EOL decision making.…”
Section: Discussionmentioning
confidence: 99%
“… 23 For example, Chinese American immigrants may have a stronger belief that family and society are held in higher regard than individuals, and attribute a higher value to collectivism of family and society rather than patient autonomy in EOL decision making. 12 Moreover, because traditional Chinese culture expects children to carry the role of protecting their parents' health, safety, and general well-being, many Chinese children may construe this responsibility as making every effort to prolong their older parents' life, which may sometimes be in opposition to their parents' own wishes. 24 These potential factors surrounding older Chinese immigrants may help explain this population's lack of engagement in ACP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park and Lee (2017) found that sibling caregivers of older Korean adults had a sense of responsibility and obligation to take care of the brother or sister that was not explicit in studies with western participants. In another study with older and younger Chinese American adults, both groups perceived advanced care planning was important; however, both groups believed it was taboo to initiate discussion as it may bring bad luck to individuals and may hasten death (Lee, Byon, Hinderer, & Alexander, 2017). Thus, discussion of smart homes for older adults’ health care may disrupt culturally appropriate communication between Asian older adults and their children.…”
Section: Health Monitoring and Privacymentioning
confidence: 99%